The effects of migration and remittances in rural Moldova - Eugene Hristev; Georgeta Mincu; Maya Sandu; Mateusz Walewski (Center for Social and Economic Research (CASE), 2009)
Remittances in Moldova reach 36% of GDP, hence they constitute an essential part of the Moldovan economy. The most visible characteristic of remittances is their unequal distribution. The analysis applying the standard Lorenz Curve proves that 75% receiving households gets only 25% of total amount being sent to the country. The way remittances are distributed does not seem to be random. Higher amounts go in general to younger and more educated households. Remittances strongly influence the economic potential of households, especially if they are high enough. They often constitute the main source of households' income, but they not discourage the members of receiving households from economic activity. It indicates that migration and working abroad is the manifest of economic activity, on the other hand it suggest that lack of employment opportunities in the country is an important reason for migration. Those who obtain remittances tend to have higher share of investments in their total household spending. Significant share of remittances for all groups is spent on education - the basic investment increasing the future competitiveness. In rural areas remittances are much more often used to improve the quality of farms than to start running other businesses. It seems that lack of infrastructure and good governance is the main reason for which educated and young emigrants sending significant amounts of money do not decide to invest them in entrepreneurial activities. Eradicating these impediments for local development should be become a highest priority.
Keywords: F22; F24; I31; J21; J61; R23; 330; Moldova; migrations; remittances; labor market; welfare; rural areas; Internationale Migration; Arbeitsmigranten; Rücküberweisungen; Ländlicher Raum; Moldawien